Effect of carbon source on biomass growth and nutrients removal of Scenedesmus obliquus for wastewater advanced treatment and lipid production. (August 2015) - Shen, Qiao-Hui; Jiang, Jia-Wei; Chen, Li-Ping; Cheng, Li-Hua; Xu, Xin-Hua; Chen, Huan-Lin
Highlights: Carbon source supplement enhanced algal growth and nutrients removal. Low concentrations of organic carbon pollutants were removed by S. obliquus . 5% CO2 bubbling accelerated biomass and lipid productivity of S. obliquus . Pollutants in a real urban wastewater were efficiently utilized by microalgae. Abstract: The combination of tertiary wastewater treatment and microalgal lipid production is considered to be a promising approach to water eutrophication as well as energy crisis. To intensify wastewater treatment and microalgal biofuel production, the effect of organic and inorganic carbon on algal growth and nutrient removal of Scenedesmus obliquus were examined by varying TOC (total organic carbon) concentrations of 20–120 mg L −1 in wastewater and feeding CO2 concentrations in the range of 0.03–15%, respectively. The results showed that the maximal biomass and average lipid productivity were 577.6 and 16.7 mg L −1  d −1 with 5% CO2 aeration. The total nitrogen, total phosphorus and TOC removal efficiencies were 97.8%, 95.6% and 59.1% respectively within 6 days when cultured with real secondary municipal wastewater. This work further showed that S. obliquus could be utilized for simultaneous organic pollutants reduction, N, P removal and lipid accumulation.